Application Of Super Encryption Using Rot 13 Algorithm Method and Algorithm Beaufort Cipher For Image Security Digital - AYUDEVIAPERTIWI; Achmad Fauzi; Siswan Syahputra (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
Digital image security is becoming increasingly critical in today's digital era, where sensitive information and data are often stored in image form. Therefore, an effective and secure encryption method is needed to protect the integrity and confidentiality of digital images. This study aims to implement a stronger security approach by combining classic encryption methods, namely the ROT13 algorithm and the Beaufort Cipher algorithm which produces an encryption called "Super Encryption". In this study, first of all, the ROT13 encryption method will be applied to randomize digital image text by shifting characters as far as 13 positions in the alphabet. Then, the Beaufort Cipher algorithm will be used to apply additional encryption to the digital image, which involves using the key as input in the encryption process. The results of this study indicate that the Super Encryption method which combines the ROT13 and Beaufort Cipher algorithms provides a higher level of security compared to using each method separately. Security testing and vulnerability analysis show that the combination of these two algorithms produces digital images that are more difficult to decrypt by commonly used decryption attacks.